Effects of left ventricular assist device implantation on respiratory drive - Tasoulis, Athanasios; Tzanis, Georgios; Vasileiadis, Ioannis; Dimopoulos, Stavros; Karatzanos, Eleftherios; Nanas, Serafim; Charitos, Christos (Health & Research Journal, 2019)
Background: Patients with heart failure (HF) suffer from ventilatory abnormalities that are related to poor prognosis. Aim: The aim of the study was to investigate the respiratory drive in HF patients early after left ventricular assist device (LVAD) implantation. Methods: We enrolled eight HF patients after LVAD (HeartMate II) implantation and 8 patients with advanced HF (control group). Patients were evaluated with cardiopulmonary exercise testing, respiratory function tests and transthoracic echocardiographic examination at 1, 3 and 6 months. Respiratory drive was estimated by the mouth occlusion pressure-P0.1 and the P0.1/Pimax ratio. Results: LVAD patients at 1, 3 and 6 months after implantation had significantly improved P0.1/Pimax% ratio (4.17±0.43 vs 3.29±1.0 vs 2.56±0.35 respectively,p<0.01) as well as significantly increased in Pimax. No changes where observed in the HF control group. A significant decrease in LVEDD, LVESD and an improvement in LVEF is also observed during follow up. Conclusions: Our results imply LVAD implantantion induces a progressive and significant improvement of respiratory drive and Left ventricle reverse remodeling during a 6 month follow-up period.